GE_GERICHTE P/4044/2013 vom 7. Juni 2013 - GE Cour de justice (2013)
CLASSEMENT DE LA PROCÉDURE; INDEMNITÉ(EN GÉNÉRAL); TORT MORAL; DÉTENTION PROVISOIRE; PROLONGATION; FAUTE PROPRE | CPP.319; CPP.429; CPP.430